We will discuss here about the general form and general term of a Geometric Progression.
The general form of a Geometric Progression is {a, ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ............}, where ‘a’ and ‘r’ are called the first term and common ratio (abbreviated as C.R.) of the Geometric Progression.
The nth or general term of a Geometric Progression
To prove that the general term or nth term of a Geometric Progression with first term ‘a’ and common ratio ‘r’ is given by t\(_{n}\) = a ∙ r\(^{n - 1}\)
Proof:
Let us assume that t\(_{1}\), t\(_{2}\), t\(_{3}\), t\(_{4}\), ................., t\(_{n}\), ............... be the given Geometric Progression with common ratio r. Then t\(_{1}\) = a ⇒ t\(_{1}\) = ar\(^{1 - 1}\)
Since t\(_{1}\), t\(_{2}\), t\(_{3}\), t\(_{4}\), ................., t\(_{n}\), ............... is a Geometric
Progression with common ratio r, therefore
\(\frac{t_{2}}{t_{1}}\) = r ⇒ t\(_{2}\) = t\(_{1}\)r ⇒ t\(_{2}\) = ar ⇒ t\(_{2}\) = ar\(^{2 - 1}\)
\(\frac{t_{3}}{t_{2}}\) = r ⇒ t\(_{3}\) = t\(_{2}\)r ⇒ t\(_{3}\) = (ar)r ⇒ t\(_{3}\) = ar\(^{2}\) = t\(_{3}\) = ar\(^{3 - 1}\)
\(\frac{t_{4}}{t_{3}}\) = r ⇒ t\(_{4}\) = t\(_{3}\)r ⇒ t\(_{4}\) = (ar\(^{2}\))r ⇒ t\(_{4}\) = ar\(^{3}\) = t\(_{4}\) = ar\(^{4 - 1}\)
\(\frac{t_{5}}{t_{4}}\) = r ⇒ t\(_{5}\) = t\(_{4}\)r ⇒ t\(_{5}\) = (ar\(^{3}\))r ⇒ t\(_{5}\) = ar\(^{4}\) = t\(_{5}\) = ar\(^{5 - 1}\)
Therefore, in general, we have, t\(_{n}\) = ar\(^{n - 1}\).
Alternate method to find the nth term of a Geometric Progression:
To find the nth term or general term of a Geometric Progression, let us assume that a, ar, ar\(^{2}\), ar\(^{3}\), a\(^{4}\), .......... be the given Geometric Progression, where ‘a’ is the first term and ‘r’ is the common ratio.
Now form the Geometric Progression a, ar, ar\(^{2}\), ar\(^{3}\), a\(^{4}\), ......... we have,
Second term = a ∙ r = a ∙ r\(^{2 - 1}\) = First term × (Common ratio)\(^{2 - 1}\)
Third term = a ∙ r\(^{2}\) = a ∙ r\(^{3 - 1}\) = First term × (Common ratio)\(^{3 - 1}\)
Fourth term = a ∙ r\(^{3}\) = a ∙ r\(^{4 - 1}\)= First term × (Common ratio)\(^{4 - 1}\)
Fifth term = a ∙ r\(^{4}\) = a ∙ r\(^{5 - 1}\) = First term × (Common ratio)\(^{5 - 1}\)
Continuing in this manner, we get
nth term = First term × (Common ratio)\(^{n - 1}\) = a ∙ r\(^{n - 1}\)
⇒ t\(_{n}\) = a ∙ r\(^{n - 1}\), [t\(_{n}\) = nth term of the G.P. {a, ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ..........}]
Therefore, the nth term of the Geometric Progression {a, ar, ar\(^{2}\), ar\(^{3}\), .......} is t\(_{n}\) = a ∙ r\(^{n - 1}\)
Notes:
(i) From the above discussion we understand that if ‘a’ and ‘r’ are the first term and common ratio of a Geometric Progression respectively, then the Geometric Progression can be written as
a, ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ................, ar\(^{n - 1}\) as it is finite
or,
ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ................, ar\(^{n - 1}\), ................ as it is infinite.
(ii) If first term and common ratio of a Geometric Progression are given, then we can determine its any term.
How to find the nth term from the end of a finite Geometric Progression?
Prove that if ‘a’ and ‘r’ are the first term and common ratio of a finite Geometric Progression respectively consisting of m terms then, the nth term from the end is ar\(^{m - n}\).
Proof:
The Geometric Progression consists of m terms.
Therefore, nth term from the end of the Geometric Progression = (m - n + 1)th term from the beginning of the Geometric Progression = ar\(^{m - n}\)
Prove that if ‘l’ and ‘r’ are the last term and common ratio of a Geometric Progression respectively then, the nth term from the end is l(\(\frac{1}{r}\))\(^{n - 1}\).
Proof:
From the last term when we move towards the beginning of a Geometric Progression we find that the progression is a Geometric Progression with common ratio 1/r. Therefore, the nth term from the end = l(\(\frac{1}{r}\))\(^{n - 1}\).
Solved examples on general term of a Geometric Progression
1. Find the 15th term of the Geometric Progression {3, 12, 48, 192, 768, ..............}.
Solution:
The given Geometric Progression is {3, 12, 48, 192, 768, ..............}.
For the given Geometric Progression we have,
First term of the Geometric Progression = a = 3
Common ratio of the Geometric Progression = r = \(\frac{12}{3}\) = 4.
Therefore, the required 15th term = t\(_{15}\) = a ∙ r\(^{n - 1}\) = 3 ∙ 4\(^{15 - 1}\) = 3 ∙ 4\(^{14}\) = 805306368.
2. Find the 10th term and the general term of the progression {\(\frac{1}{4}\), -\(\frac{1}{2}\), 1, -2, ...............}.
Solution:
The given Geometric Progression is {\(\frac{1}{4}\), -\(\frac{1}{2}\), 1, -2, ...............}.
For the given Geometric Progression we have,
First term of the Geometric Progression = a = \(\frac{1}{4}\)
Common ratio of the Geometric Progression = r = \(\frac{\frac{-1}{2}}{\frac{1}{4}}\) = -2.
Therefore, the required 10th term = t\(_{10}\) = ar\(^{10 - 1}\) = \(\frac{1}{4}\)(-2)\(^{9}\) = -128, and, general term, t\(_{n}\) = ar\(^{n - 1}\) = \(\frac{1}{4}\)(-2)\(^{n - 1}\) = (-1)\(^{n - 1}\)2\(^{n - 3}\)
● Geometric Progression
11 and 12 Grade Math
From General Form and General Term of a Geometric Progression to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Jul 18, 24 03:08 PM
Jul 18, 24 01:19 AM
Jul 18, 24 01:15 AM
Jul 18, 24 01:02 AM
Jul 18, 24 12:45 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.